Features of family anxiety and marital relationship in individuals married to HIV-infected injecting drug users - V. M. Podolyan (Kazimierz Wielki University, 2017)
The objective: to study the peculiarities of family anxiety and marital relations among persons married to an HIV-infected injection drug user (IDU) in order to understand possible targets for further medical and psychological work with this contingent. Contingent and methods. In 2010 - 2017 on the basis of the Vinnitsa Regional Drug Treatment Center "Sociotherapy" a clinical-psychopathological and psychodiagnostic survey of 113 HIV-infected IDUs and their family members was conducted. Results On the basis of analysis of the characteristics of family anxiety and the state of marital relationships in families of HIV-infected IDUs, signs of their distortion are established in almost all surveyed. Marital partners of HIV-infected IDUs were characterized by high general family anxiety, due to high indicators for all its components - fault, anxiety and stress. The married relationship of the surveyed was based on a reduced (in most cases) one-component love. The feeling of the majority of the partners of HIV-infected IDUs, as it seemed, was a duty, through which they did not break the relationship with proband, was interpreted by us as a manifestation of the co-dependence of these individuals. Consequently, the results of the study indicated that they had family and marital maladaptation as a consequence of co-dependent relationships. The data obtained should be taken into account when planning a medical-psychological support event for this contingent.